Customized Packaging Support System Hotel - Pribadi, Yoke; Gunawan, Agus; Caroline, Angela; Adrian, Jeff; Devina, Sheryl (Jurnal Administrasi Bisnis, 2016)
Advances in technology are causing transport becomes cheaper and government support to promote tourism has positive impact in the hospitality business, even in West Java, there are around 1,649 registered hotels. Various hotels are competing in various forms of strategies. One strategy used is rife customer intimacy strategy in the form of packages that provide customized according to the preferences of the target customer.Research type is qualitative that use five hotel as samples. Data collected through interviews, FGD (Focus Group Discussion), and evaluation of the Standard Operating Procedures and systems used by the hotel. Analyze data using MIT 90s Framework and BPMN (Business Process Modeling and Notation) to determine the systems needed by the hotel as well as describe the proposed system of this research.This research focuses on designing information systems that can support hotel in offering customized packages.Â Keywords : Information System, Customer Packages